Fulfillment of the Rights and Obligations of Husband and Wife in Farming Families in Sukoharjo Village, Kandangserang District - Jumailah; Efa Hindayati (Asian Journal of Law and Humanity, 2023)
The rights and obligations of husband and wife are legal consequences arising from the marriage bond. Sukoharjo Village, Kandangserang District, Pekalongan Regency, farmers' wives also work to earn a living because the wives feel that their husbands are neglecting their obligations to earn a living. Wives who work as agricultural laborers make husbands feel that their wives are neglecting their obligations to take care of the household. The research method that the author uses is qualitative research using empirical juridical research with a sociological approach. The results of the research are: (1) Husbands and wives in farming families in Sukoharjo Village have tried to carry out their obligations as well as possible. So that each of them will get their rights well too. (2) The factor that causes a husband to feel that he is not getting his rights is the absence of his wife to take care of household needs, her own needs and her children's needs. The factor that causes the wife to feel that she does not get her rights is because the husband's work as a farmer is not demanding, sometimes the harvest is successful but sometimes it also fails. (3) Judging from Law no. 16 of 2019, Compilation of Islamic Law, the opinion of Qurais Shihab, and Madzhab Ulama that the husband has carried out his obligations as head of the family in earning a living and the wife also takes care of household needs well amidst her busy life as a farm worker.